National development strategy : (2001-2010) a policy framework : eradicating poverty and unifying Guyana : a civil society document (the Secretariat GeorgetownGY, 2000)
Seeks to attain the highest rates of economic growth that are possible; to eliminate poverty in Guyana; to achieve geographical unity; to attain an equitable geographical distribution of economic activity; and, to diversify the economy.
Located in the Office of the Secretary General